Pengaruh Penerapan Sistem Ekonomi Syariah Di Kalangan Remaja - Andini; Adelia Rahma Aryadi (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2022)
In our daily life we ​​are always closely related to the economic system. At this time the Islamic economic system has begun to be used in economic activities. If the sharia economic system is applied to the community, especially among teenagers, this system will become more well known. Moreover, the role of youth as agents of change is very important. Therefore, in this discussion we will find out about the application of Islamic economics and how it affects teenagers. This study uses a qualitative method, while the data collection techniques are in the form of questionnaires or questionnaires. Respondents from this study were 31 students. Based on the results of the study, the Islamic economic system is very influential on daily life, especially among teenagers. Because the Islamic economic system is in accordance with the conditions set out in Islam, which in its implementation prioritizes the welfare of the entire community. This can be realized if the application of Islamic economics is started from among teenagers.